Reducing Uncertainty In Log Analysis Due To Presence Of Heavy-Conductive Minerals In Sendimentary Rocks - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2000)
Presence of heavy-conductive mineral(s) in formation rocks tends to provide negative influence to some log readings especially the resistivity log. With regard to its function in log analysis, any distortion in resistivity log readings will certainly lead to potential misinterpretation on petrophysical properties such as water saturation (S.) Therefore a method dedicated to minimizing the effect is indeed necessary.This paper presents results of a study on presence of heavy-conductive minerals, distributed in structural form, on resistivity reading. Based on analogy and expansion of a structural clay distribution model, a correction method plus its application procedure have been proposed. Since the method is develop using an approach that is considered valid in general term it is, therefore, conceptually applicable to any field cases as long as its theoretical conditions are met. In order to make application of the method easier it has also been presented in form of nomographs.Application of the method on log analysis of two wells in West Java has proved itself well in which corrections on calculated water saturation have yielded values that are more consistent when compared to production test data. The method is also prepared in a manner that it can be easily integrated into standard log analysis practices.